Tafsir Tarbawi Teaching Strategy to Improve Students' Religious Attitudes - Abdah Muhammad Hasan; Iskandar Mirza, (Penerbit Hellow Pustaka, 2025)
This paper discusses strategies for teaching tafsir tarbawi in improving students' religious attitudes. The tarbawi tafsir teaching strategy is defined as a Qur'an-based approach that aims to create a conducive learning environment to support the achievement of Islamic educational goals. By examining the main elements of teaching strategy—such as setting teaching goals, choosing a learning system approach, determining methods, and evaluating learning success—this paper outlines the potential of tarbawi's interpretive approach in shaping religious awareness. Research is carried out qualitatively using a literature study approach. The results show that the tarbawi interpretation teaching strategy implemented through understanding the concepts of Al-Hikmah, Al-Mau'idzah Al-Hasanah, and Al-Mujjadi (QS An-Nahl: 125) is able to provide a holistic learning foundation, covering cognitive, affective and conative aspects. The implementation of this strategy supports the development of balanced religious attitudes of students, both individually and socially, so that they are more beneficial to religion and society.